Navigation of an underwater robotics vehicle using an inertial navigation system and a global positioning system - Lim, Song Heng. (2008)
The capabilities and performance of both the standard GPS and the differential global positioning system (DGPS) are examined in detailed. The accuracy, stability and repeatability of the standard GPS and DGPS system are also investigated in this thesis.